The development of mobile money services and financial inclusion in Zimbabwe - Chingono, Kudzaishe Emily (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Purpose- The use of mobile phones in Zimbabwe fostered the development of various financial innovations, such as mobile money services. It is important to note that the use of mobile money services in Zimbabwe has gradually increased. This study was carried out to determine the relationship between the development of mobile money services and financial inclusion in Zimbabwe. The main goal was to determine if there is a correlation between financial inclusion and the development of mobile money services. Design and Methodological approach: This study used a quantitative research design in which time series data was used to generate the analysis. The data used in the study covered a period of 20 years, starting from 2000 to 2020 on a yearly basis. Auto Regressive Distributed Lag (ARDL) Model was used to analyze the relationship. Findings: The ARDL study results showed that in the long run, there is no statistically significant correlation between the development of mobile money services and financial inclusion, and this is suggested by the long-term relationship between the two variables over a period of 20 years. In the short run, the study findings showed that the development of mobile money services have a positive significant influence on financial inclusion with. Therefore, increase in mobile money usage was associated with increase in financial inclusion. Between the period 2000 and 2020, the major determinants of mobile moneys services are age, number of ATMs, financial literacy, income level and mobile phone penetration. The tests also showed that these variables significantly and positively influenced use of mobile money as a financial inclusion tool in Zimbabwe (p<.05). Research Limitations: The study did not find a lot of current relevant literature that would explain the relationship between mobile money services and financial inclusion. Majority of the work was carried out in other countries, and little was covered in Zimbabwe. Practical Implications: The study results implies that government should put in place measure to ensure the expansion of mobile money services in the rural areas. The mobile telecommunication firms should ensure increased mobile phone penetration.
Keywords: Mobile commerce Zimbabwe; Financial inclusion; Automated tellers; Financial literacy; Education Social aspects -- South Africa; Technology and older people -- South Africa